Research Trend of Integration of Problem Based Learning in Laboratory Activities: A Bibliometric Analysis - Aulia Ajizah; N. Nahadi; Chairil Faif Pasani; Encep Syarief Nurdin (Jurnal Penelitian Pendidikan IPA, 2024)
This article is written to analyze the research trends regarding the integration of the Problem Based Learning (PBL) model in laboratory practical activities over the past 10 years (2014–2023). The method employed is Bibliometric Analysis, supported by the VOSviewer application. The analysis focused on titles and abstracts, encompassing 961 scientific articles from international journals indexed in Scopus over the last decade. Data collection was performed through searches using the keyword "Problem Based Learning in Laboratory Activities." The search results reveal network formation, overlays, and trend direction graphs over the past 10 years. The research yields the following data: 1) The total number of publication articles based on keywords is 961 documents, which are filtered down to 453 documents, 2) The country with the highest contribution to published articles is the USA with 194 documents, 3) Co-occurrence analysis shows variations in article topics with six clusters, and 4) Overlay Visualization indicates that articles on laboratory activities tend to focus on the learning system, student-related aspects, curriculum, and problem-solving